The theoretical basis for determining the stress-strain state of the clay rock mass as a visco-elasto-plastic environment - Tyutkin, O. L. (Science and Transport Progress, 2008)
In the article the theoretical bases of determination of the stressed-and-strained state of clay massif from positions of the theory of viscous-elastic-plastic medium are presented.